Biomedical Engineering in Nepal: Opportunities and Challenges - Dabadi, Sambardhan; Dhungel, Raju raj (Annapurna Journal of Health Sciences, 2023)
Biomedical engineering is the blend of engineering and medical science, professional with a combination of knowledge of various engineering discipline to improve health care and quality of life. While biomedical engineering formally came up as major course in 1950s, the course started in Nepal just a decade back with its importance being acknowledged and biomedical engineers have been recruited by various institutes. Accounting for artificial intelligence, robotic surgery, 3-d printing, which are believed to be the future of medical science, it is necessary to strengthen the biomedical engineering. This article aims to highlight the overview as well as opportunities and challenges of biomedical engineering in Nepal.